BASIS DATA UNTUK MENGEMBANGKAN SISTEM INFORMASI SEKOLAH - Ahmad Abu Hamid (Jurnal Kependidikan, 2008)
The purpose of this policy study was for identifying database thatcould be used to develop a school information system (SIS) and foridentifying external and internal stake holders that could be used asdata and information to be filed in SIS. The results of the study couldbe used to make recommendation for schools about the merits ofbuilding an SIS, intranet, and internet system. As a case study, thisresearch was held in State Senior High School 1, Jetis, Bantul. Datawere gathered from interviews and documentation. Evaluative analysiswas used to yield research results and descriptive analysis was used toformulate the recommendation to be extended to the schools. Dataanalyses and discussion brought about these conclusions andrecommendation:(1) Structure database were available that could beused to develop an SIS, (2) Those database could be categorized intospecific data and information about the institution, curriculum,school’s infrastructure, teachers, instruction, grades, students, newstudent admission process, alumnus, school’s library, worker, andschool’s monetary, (3) Teachers, students, functionaries of StateSenior High School 1, Jetis and the public could access data andinformation kept in the SIS, and (4) The schools may be expected tobuild an SIS, intranet, and internet.